Long segment detection of HTLV-1 genome based on the fluorescence quenching technique. Issue 12 (December 2018) - Ghobadi, Mohadeseh Zarei; Mozhgani, Sayed-Hamidreza; Hakimian, Fatemeh; Norouzi, Mehdi; Rezaee, Seyed Abdolrahim; Ghourchian, Hedayatollah
Abstract: Detecting fluorescence changes due to energy transfer between a quencher and fluorophore is a common method used for the fluorescence-based biosensors. In the present report, a new biosensor for long segment detection of the human T cell-lymphotropic virus 1 genome was constructed based on the fluorescence quenching of graphene oxide by gold nanoparticles. The fluorescence signal of unmodified graphene oxide was measured before and after hybridization of target and probes functionalized with gold nanoparticles. The limit of detection of the biosensor was determined to be around 10 pg/mL. The specific design for long segment of target assures the selectivity of biosensor. Our results proposed that further development may be useful to detect other viruses.